Definition of the observer/identifier and the algorithms used - Hafi, Mahdi (Aljameai, 2025)
Abstract: The ability to estimate unknown system states and parameters is an essential requirement in control theory. Often system parameters are partially known and some of the states are inaccessible. This indicates that an Observer/Identifier is needed so that a control strategy can be applied effectively. An observer is a system whose state variables are the estimates of the state variables of the unknown system. Similarly, an Identifier is a system whose state variables are the estimates of the unknown system parameters. The ability to reconstruct the system states and parameters from the I/O data requires that all of the states must be observable. An on-line estimation and identification is usually desired. The success of an adaptive observer/identifier depends very much on the choice of the system model representing the unknown system. The choice of the order of the system model and whether the system model is time-variant or not, usually depends on a prior knowledge of the system dynamics and/or the study of the input-output data, such as frequency response, time domain response, etc. Once a system model is selected, an observer/identifier which usually adopts and extends an existing algorithm is developed. المستخلص: تُعد القدرة على تقدير حالات النظام ومعاملاته غير المعروفة من المتطلبات الجوهرية في نظرية التحكم. ففي العديد من التطبيقات، تكون بعض معاملات النظام معروفة جزئياً، بينما تكون بعض حالاته غير قابلة للقياس المباشر. وهو ما يستدعي تطوير مراقب/مُعرّف يمكن من خلاله تنفيذ استراتيجية تحكم فعّالة. يُعرف المراقب على أنه نظام تكون متغيرات حالته بمثابة تقديرات لحالات النظام غير المعروفة، في حين يُستخدم المُعرّف لتقدير المعاملات غير المعروفة للنظام. ويتطلب تحقيق القدرة على إعادة بناء حالات النظام ومعاملاته انطلاقاً من بيانات الإدخال والإخراج وأن تكون جميع الحالات قابلة للمراقبة. وعادةً ما يُفضّل أن تتم عملية التقدير والتعريف بصورة آنية. يعتمد نجاح المراقب/المُعرّف التكيفي إلى حد كبير على اختيار نموذج مناسب للنظام المجهول. ويتوقف تحديد رتبة النموذج، وكذلك ما إذا كان النموذج متغيراً زمنياً أم لا، على المعرفة المسبقة بديناميكية النظام أو من خلال تحليل بيانات الإدخال/الإخراج، مثل استجابة التردد أو استجابة الزمن، إلخ. وبمجرد تحديد نموذج النظام المناسب، يتم تطوير مراقب/مُعرّف يستند في الغالب إلى خوارزمية قائمة يتم تعديلها أو توسيعها لتتناسب مع خصائص النظام قيد الدراسة.